Pemurnian Fikosianin dari Spirulina platensis dengan Metode Liquid Biphasic Flotation (LBF) dan Penentuan Aktivitas Antioksidannya - Elise, Cori Yolanda; Syafrizayanti, Syafrizayanti; Salim, Marniati (Universitas Andalas, 2021)
Phycocyanin from Spirulina platensis (S. Platensis) is a pigment-complex protein belong to the light-harvesting phycobiliprotein family. The pigments have high economic value as a natural blue dye as well as the source of antioxidants and anticancer. Production of pure natural phycocyanin remains in high demand. Therefore, this study aimed to obtain phycocyanin with high purity values using modified liquid biphasic flotation (LBF) system and tested for DPPH (1,1-diphenyl-2-pycrilhydrazil) radical scavenging activity. This study produced high purity phycocyanin with purification fold 3.041 Â± 0.04 and recovery yields approximately about 70.881%. Purified phycocyanin showed scavenging activity with IC50 ofÂ Â 338.585 mg/mL. Thus, the LBF system yielded high purity phycocyanin pigments.